Efficiency analysis of solar farms by UAV-based thermal monitoring - Akay, Semih Sami; Özcan, Orkan; Özcan, Okan; Yetemen, Ömer (Elsevier BV, 2024)
Solar energy is a rapidly growing industry, and the performance analysis and maintenance of solar farms are crucial for ensuring their photovoltaics efficiency and longevity. In this context, many solar farms are established and it is crucial for energy producers to operate these farms efficiently. However, control of solar degradation panels locally takes time and control procedures are a challenge for the producers particularly for large farms. In recent years, the use of unmanned aerial vehicles equipped with thermal imaging sensors has emerged as a promising technique for monitoring solar farms. Herein, degradation inspection and efficiency analyses of the solar panels can be effectively conducted by mapping thermal orthomosaic data. In this study, thermal images were obtained for orthomosaic data production by conducting photogrammetric flights with a real time kinematic enabled unmanned aerial vehicles on a solar farm. The solar panels were divided into segments by the segmentation process and photovoltaics efficiency was calculated for each panel based on solar energy. The photovoltaics efficiency was monitored to vary at most 1.22 % throughout the day with the maximum efficiency reaching 18.25 % in the afternoon, and the minimum efficiency dipping to 17.03 % midday. Close efficiency values were acquired in the morning and afternoon with a difference not exceeding 0.12 %. As such, the damage conditions of panels can be identified by designating the ones with the lowest efficiency. Thus it can be deduced that rapid, cost effective and feasible assessment of solar farms may be possible by unmanned aerial vehicle-based thermal monitoring while bringing forth more sensitive future predictions.
Keywords: Solar farm; Thermal monitoring; UAV; PV efficiency; Solar power; TA1-2040; Engineering (General). Civil engineering (General)